Shakespeare Comes to Bengal - Chaudhuri, Sukanta (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
India has the longest engagement with Shakespeare of any non-Western country. In the eastern Indian region of Bengal, contact with Shakespeare began in the eighteenth century. His plays were read and acted in newly established English schools, and performed professionally in new English theatres. A paradigm shift came with the foundation of the Hindu College in Calcutta in 1817. Shakespeare featured largely in this new ‘English education’, taught first by Englishmen and, from the start of the twentieth century, by a distinguished line of Indian scholars. Simultaneously, the Shakespearean model melded with traditional Bengali popular drama to create a new professional urban Bengali theatre. The close interaction between page and stage also evinced a certain tension. The highly indigenized theatre assimilated Shakespeare in a varied synthesis, while academic interest focused increasingly on Shakespeare’s own text. Beyond the theatre and the classroom, Shakespeare reached out to a wider public, largely as a read rather than performed text. He was widely read in translation, most often in prose versions and loose adaptations. His readership extended to women, and to people outside the city who could not visit the theatre. Thus Shakespeare became part of the shared heritage of the entire educated middle class. Bengali literature since the late nineteenth century testifies strongly to this trend, often inducing a comparison with the Sanskrit dramatist Kalidasa. Most importantly, Shakespeare became part of the common currency of cultural and intellectual exchange.